Opinions of Korean science editors on open access policies, editorial difficulties, and government’s support for publishing - Sun Huh; Hye-Min Cho; Hyungsun Kim (Science Editing, 2015)
The Korean government has supported scholarly scientific journal publishing since 1971 through the Korean Federation of Science and Technologies (hereafter the Federation). To ensure that this funding is used as efficiently as possible, the views of science editors should be considered. This study measured the opinions of Korean science editors on open access policies, difficulties during editing, and the government’s support for publishing. From November 28 to December 10 of 2013, web survey invitations were emailed to 368 journal editors listed by the Federation. The web survey tool Surveymonkey was used to create a questionnaire that consisted of ten items, including the research category for each journal. Out of the 368 editors, 82 responded to the survey (22.3%). Sixty-nine editors (84.1%) had already accepted the open access or free access policy. Of the 13 editors of journals without open/free access policies, seven hoped to adopt a policy within three years. The most difficult tasks in journal publishing were adding a journal to international databases, operating with an inadequate budget, and recruiting professional manuscript editors. Editors want the Federation to increase budgets to cover full-text extensible markup language production costs, to provide guidelines for adding journals to international databases, and to provide programs for training professional manuscript editors and a plagiarism detection system. Most science editors in Korea have already adopted an open/free access policy. Training professional manuscript editors, using plagiarism detection system, and producing full-text extensible markup language should be considered as important items for journal publishing support from the Federation.